“Ocupa Rua”: : a project for reusing the streets of downtown São Paulo starting with the Covid-19 pandemic. - Erthal, Claudia (Latitude, 2022)
This article proposes a reflection based on the concept of the five skins created by the Austrian architect and artist Friedensreich Hundertwasser, having as its object the pilot project “Ocupa Rua”, carried out in São Paulo, on new uses of an urban center and the layers of perception and experience that this project can provide. It includes walks, readings and the use of mobile devices by users/ walkers as a form of communication and social belonging, generating a lively communicational dynamic. The presence of the user who seems to collaborate with the creation of new reading layers for the city permeates this text. It is believed that it goes beyond the commercial purpose and, by containing concepts of revitalization as a source of possibilities for reusing the streets; it becomes also a form of reuse and of the city as a whole from this starting point.